2018
DOI: 10.1136/vr.104388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiography as a screening method for detection and characterisation of congenital vertebral malformations in dogs

Abstract: Congenital vertebral malformations (CVM) are common in brachycephalic 'screw-tailed' dogs; they can be associated with neurological deficits and a genetic predisposition has been suggested. The purpose of this study was to evaluate radiography as a screening method for congenital thoracic vertebral malformations in brachycephalic 'screw-tailed' dogs by comparing it with CT. Forty-nine dogs that had both radiographic and CT evaluations of the thoracic vertebral column were included. Three observers retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
(63 reference statements)
0
19
2
Order By: Relevance
“…13 Although it is possible that the three assessed brachycephalic breeds are predisposed for lumbosacral spinal bifida, it is likely that the use of cross-sectional imaging has contributed to the high prevalence in this study as previously suggested. 35 Analysis of previous reports suggests a predisposition of English Bulldogs for lumbosacral spina bifida, 14 which could not be confirmed in our study. It should, however, be emphasized that previous reports have focused on clinically affected dogs, while this study included only apparently neurologically normal dogs.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…13 Although it is possible that the three assessed brachycephalic breeds are predisposed for lumbosacral spinal bifida, it is likely that the use of cross-sectional imaging has contributed to the high prevalence in this study as previously suggested. 35 Analysis of previous reports suggests a predisposition of English Bulldogs for lumbosacral spina bifida, 14 which could not be confirmed in our study. It should, however, be emphasized that previous reports have focused on clinically affected dogs, while this study included only apparently neurologically normal dogs.…”
Section: Discussioncontrasting
confidence: 90%
“…Spina bifida was a rather uncommon finding in this study but was still markedly higher than previously suggested with 0.007% independent of the breed . Although it is possible that the three assessed brachycephalic breeds are predisposed for lumbosacral spinal bifida, it is likely that the use of cross‐sectional imaging has contributed to the high prevalence in this study as previously suggested . Analysis of previous reports suggests a predisposition of English Bulldogs for lumbosacral spina bifida, which could not be confirmed in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…The prevalence of CTV is relatively low in the adult animal and human populations. Prevalence in dogs is 2.1-14%, where pugs seem to be overrepresented, in cats 1%, and in the human population 0.04-6.2% [27,35]. CTV was also detected with a higher incidence in fossil Pleistocene rhinoceroses and mammoths [36,37].…”
Section: Discussionmentioning
confidence: 96%
“…Low variability of cervical vertebrae number in the adult population is usually explained by the Hox gen pleiotropic function. Numerical variants in the cervical vertebral column increase risk for prenatal mortality and neonatal cancer [7,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the terminology and classification are debated, hemivertebra are considered a common type of congenital vertebral body malformation . Thoracic hemivertebrae occur commonly in clinically normal small breed brachycephalic dogs and therefore should be considered incidental imaging findings in the majority of dogs in which they are identified . Hemivertebrae can be associated with an abnormal dorsal (ie, kyphosis) or lateral (ie, scoliosis) curvature of the vertebral column and have the potential to alter spinal biomechanics, contribute to degenerative spinal conditions, or result directly in clinical signs of spinal cord dysfunction .…”
Section: Introductionmentioning
confidence: 99%